Fecal elastase test in diagnosing exocrine pancreatic insufficiency: The Web of Science and Scopus bibliometric analysis (1984–2024) - Bazargaliyev, Yerlan; Makashova, Mengtay; Kudabayeva, Khatimya; Kosmuratova, Raikul; Kurmangaliyev , Kairat (Acta Biomedica Atenei Parmensis, 2025)
Background: Exocrine pancreatic insufficiency (EPI) is a condition characterized by impaired nutrient digestion due to insufficient enzyme secretion, leading to steatorrhea and weight loss. Fecal elastase (FE) is a reliable non-invasive biomarker for diagnosing EPI and detecting enzymatic dysfunction.Aims and Methods: This study provides a bibliometric analysis of the role for the diagnosis of FE, using Scopus and Web of Science databases (1984–2024). Data merging, statistical analyses, and visualizations were conducted using RStudio and the Bibliometrix R package.Results: A total of 385 publications from 188 sources were analyzed. The peak year was 2022 with 38 publications, followed by a decline to 17 in 2023. The United States leads with 136 publications and international cooperation with 26 joint projects, especially with Poland, Italy and the UK. Germany showed the highest scientific citations impact (2,024). The most prolific institutions were Haukeland University Hospital in Norway and Poznan University of Medical Sciences in Poland. The Pancreatology journal stand out as one of the leading scientific publications on EPI.Conclusions: Overall, this analysis provides a comprehensive overview of the research landscape, identifies critical areas for future investigation, and emphasizes the need to strengthen interdisciplinary collaboration to drive global advancements in the diagnosis of EPI.